Evaluation of Green Public Road Procurement in Australia: Current Practices and Gaps - Lehtiranta, L.; Hampson, Keith D.; Kenley, R. (QUT Eprints, 2012)
Public road authorities have a key responsibility in driving initiatives for reducing greenhouse gas (GHG) emissions in the road construction project lifecycle. A coherent and efficient chain of procurement processes and methods is needed to convert green policies into tangible actions that capture the potential for GHG reduction. Yet, many infrastructure clients lack developed methodologies regarding green procurement practices. Designing more efficient solutions for green procurement requires an evaluation of the current initiatives and stages of development. A mapping of the current GHG reduction initiatives in Australian public road procurement is presented in this paper. The study includes the five largest Australian state road authorities, which cover 94% of the total 817,089 km of Australian main roads (not local) and account for 96% of the total A$13 billion annual major road construction and maintenance expenditure. The state road authorities’ green procurement processes and tools are evaluated based on interviews and a review of documents. Altogether 12 people, comprising 1-3 people of each organisation, participated in the interviews and provided documents. An evaluation matrix was developed for mapping the findings across the lifecycle of road construction project delivery.The results show how Australian state road authorities drive decisions with an impact on GHG emissions on the strategic planning phase, project development phase, and project implementation phase. The road authorities demonstrate varying levels of advancement in their green procurement methodologies. Six major gaps in the current green procurement processes are identified and, respectively, six recommendations for future research and development are suggested. The greatest gaps remain in the project development phase, which has a critical role in fixing the project (GHG reduction) goals, identifying risks and opportunities, and selecting the contractor to deliver the project. Specifically, the role of mass-haul optimisation as a part of GHG minimisation was reviewed, and mass-haul management was found to be an underutilised element with GHG reduction potential.